Más allá del orientalismo: leer a Marx entre Chakrabarty y Aricó - Starcenbaum, Marcelo (2020)
Beyond the differences between the intellectual and political practices of Dipesh Chakrabarty and José Aricó, the work of both authors represent a common way of intervening in the discussion about Marx's Orientalism. Simultaneously with Said's work and the debates generated by it, the Indian historian and the Argentine intellectual developed a reading of Marx focused on the ambivalences of the German thinker regarding non-European societies. Differentiated from the hypothesis of a necessary Eurocentrism in the configuration of Marxist theory, the two authors endeavored to demonstrate the need for Marxist concepts to account for peripheral realities. In the case of Chakrabarty, rescuing the narrative of capital but opening the Marxist corpus to the problem of historical difference. In the case of Aricó, destabilizing the Marxist tradition through the recovery of a Marx interested in the specificities of non-European societies. Through these operations, Chakrabarty and Aricó developed a critical movement within Marxism that involved maintaining a materialistic position but also opening up to national and regional singularities.